A "fully upper extremity" bailout of direct transaxillary large bore arterial access: A refinement within arm's reach?. Issue 6 (1st July 2021) - Mathur, Moses; Zack, Chad J.; Heatley, Ashley; Rhodes, Denise; Yamane, Kentaro; Gilchrist, Ian C.; Kozak, Mark
Abstract: Contemporary direct ("fully percutaneous") transaxillary (TAx) large‐bore arterial access technique advocates for a 0.018" wire to be passed from femoral arterial access to axillary artery to serve percutaneous bailout options. However, in certain patients, avoiding femoral arterial access entirely may be desired. We describe the merits of a "fully upper extremity" (FUE) bailout approach, as a refinement to previously described direct TAx technique.